The Effect of Intellectual Capital, Work Environment and Work Motivation of Behavior Organizational Citizenship and Employee Performance in PT. Japfa Comfeed Indonesia, Tbk Makassar Branch - Dwi Ningrum; Sitti Haerani; Musran Munizu (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aims to determine and analyze the effect of intellectual capital, work environment and motivation on organizational citizenship behavior, know and analyze the effect of intellectual capital, work environment and motivation on employee performance, and analyze the effect of organizational citizenship behavior on employee performance. To implement these objectives the data collection techniques are used through observation, questionnaires and documentation, using the Partial Least Square (PLS) analysis method. PLS, descriptive, hypothesis testing, Measurement Model (Outer Model), validity test, reliability test, Structural Model (Inner Model). The results showed that intellectual capital, work environment and motivation significantly influence organizational citizenship behavior. The influence of intellectual capital on employee performance, which in this study empirically, intellectual capital, work environment and work motivation have a positive and significant effect on employee performance, which means that intellectual capital provides a beneficial influence in improving employee performance at PT. Japfa Comfeed Indonesia, Tbk. Makassar branch. The results of the study that organizational citizenship behavior provides a significant influence in improving employee performance at PT. Japfa Comfeed Indonesia, Tbk. Makassar branch.